Syntactic and semantic features of English collocations containing the word “free” with reference to the Vietnamese equivalents / Nguyễn Thị Ngọc Dung; Supervisor: Dr Phạm Thị Tuyết Hương - Nguyễn, Thị Ngọc Dung
Collocation is a big area in linguistics, it has become the subject of a linguistic study only recently, and it arouses a growing interest in numerous linguists and is defined in various ways. However, Vietnamese students meet difficulties when using English collocations. Therefore this paper aims at investigating “The syntactic and semantic features of English collocations containing the word “free” with reference to the Vietnamese equivalents.” It was conducted with the hope of finding out the equivalents of the collocations containing the word “free” in Vietnamese. The result of the thesis can be applied as a generic framework or a model for teaching English collocations in secondary and high schools. Data used for analysis in this study were mainly collected from books, literary works, and dictionaries. Data for analysis were based on descriptive, quantitative, qualitative and contrastive methods.